A Malay version of the Child Oral Impacts on Daily Performances (Child-OIDP) index: assessing validity and reliability - Mohd Yusof, Zamros Yuzadi; Jaafar, Nasruddin (BMC, 2012)
Background: The study aimed to develop and test a Malay version of the Child-OIDP index, evaluate its psychometric properties and report on the prevalence of oral impacts on eight daily performances in a sample of 11-12 year old Malaysian schoolchildren. Methods: The Child-OIDP index was translated from English into Malay. The Malay version was tested for reliability and validity on a non-random sample of 132, 11-12 year old schoolchildren from two urban schools in Kuala Lumpur. Psychometric analysis of the Malay Child-OIDP involved face, content, criterion and construct validity tests as well as internal and test-retest reliability. Non-parametric statistical methods were used to assess relationships between Child-OIDP scores and other subjective outcome measures. Results: The standardised Cronbach's alpha was 0.80 and the weighted Kappa was 0.84 (intraclass correlation = 0.79). The index showed significant associations with different subjective measures viz. perceived satisfaction with mouth, perceived needs for dental treatment, perceived oral health status and toothache experience in the previous 3 months (p<0.05). Two-thirds (66.7) of the sample had oral impacts affecting one or more performances in the past 3 months. The three most frequently affected performances were cleaning teeth (36.4), eating foods (34.8) and maintaining emotional stability (26.5). In terms of severity of impact, the ability to relax was most severely affected by their oral conditions, followed by ability to socialise and doing schoolwork. Almost three-quarters (74.2) of schoolchildren with oral impacts had up to three performances affected by their oral conditions. Conclusion: This study indicated that the Malay Child-OIDP index is a valid and reliable instrument to measure the oral impacts of daily performances in 11-12 year old urban schoolchildren in Malaysia.